2022
DOI: 10.3390/brainsci12020249
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Sources of Respiratory Mechanosensation, Laterality, and Emotion: An MEG Study

Abstract: Airway obstruction activates mechanoreceptors that project to the cerebral cortices in humans, as evidenced by scalp encephalography recordings of cortical neuronal activation, i.e., respiratory-related evoked potential (RREP). However, neural evidence of both high spatial and temporal resolution of occlusion-elicited cortical activation in healthy individuals is lacking. In the present study, we tested our hypothesis that inspiratory mechanical stimuli elicit neural activation in cortical structures that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Based on the activated areas elicited by the paired inspiratory occlusion paradigm in the three conditions, it can be inferred that these brain regions, including the thalamus, hippocampus, sensorimotor cortex, temporal gyrus, frontal gyrus, and cingulate cortex, are involved in mediating respiratory gating functions. This view is consistent with our previous study (Chan et al, 2022a) and is further supported by another study examining voluntary breathing (McKay et al, 2003). Both previous studies demonstrated comparable brain activation patterns than the present study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Based on the activated areas elicited by the paired inspiratory occlusion paradigm in the three conditions, it can be inferred that these brain regions, including the thalamus, hippocampus, sensorimotor cortex, temporal gyrus, frontal gyrus, and cingulate cortex, are involved in mediating respiratory gating functions. This view is consistent with our previous study (Chan et al, 2022a) and is further supported by another study examining voluntary breathing (McKay et al, 2003). Both previous studies demonstrated comparable brain activation patterns than the present study.…”
Section: Discussionsupporting
confidence: 94%
“…One set of ROIs were defined based on the between-condition contrast maps (Contrast N–F compared with Contrast P–F ). In addition, ROIs from the automated anatomical labeling (AAL) templates were chosen on the basis of previous studies to test the effects of emotional contexts on paired-occlusion elicited brain areas, which included bilateral anterior cingulate cortex, insula, middle cingulate cortex, thalamus, precentral cortex, postcentral cortex, and calcarine fissure ( Tzourio-Mazoyer et al, 2002 ; Chan et al, 2016 , 2019 , 2022b , a ).…”
Section: Methodsmentioning
confidence: 99%